2022
DOI: 10.1007/s13762-022-04314-5
|View full text |Cite
|
Sign up to set email alerts
|

Short-term effect of COVID-19 lockdowns on atmospheric CO2, CH4 and PM2.5 concentrations in urban environment

Abstract: The COVID-19 pandemic has changed all areas of human activity as it forced the authorities around the world to enact unprecedented restrictions such as "lockdowns". The low economic activity reduced the anthropogenic impact on the environment, in particular, greenhouse gases and aerosols emissions were decreased. However, the associated change in air quality is difficult to directly observe and quantify, since concentrations of these components in urban areas are affected by many other factors. In this work st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Continuous monitoring of atmospheric CO2, CH4 mole fractions has been carried out an urban monitoring site at the Institute of Industrial Ecology of the Ural Branch of Russian Academy of Sciences (IIE UB RAS), Yekaterinburg (56.85° N; 60.65° E) since 2015 [4]. From September 2021, measurements were organized at a background station.…”
Section: Methodsmentioning
confidence: 99%
“…Continuous monitoring of atmospheric CO2, CH4 mole fractions has been carried out an urban monitoring site at the Institute of Industrial Ecology of the Ural Branch of Russian Academy of Sciences (IIE UB RAS), Yekaterinburg (56.85° N; 60.65° E) since 2015 [4]. From September 2021, measurements were organized at a background station.…”
Section: Methodsmentioning
confidence: 99%
“…These measures changed people's lifestyles and work patterns and affected industrial production [17][18][19]. Recent studies have shown that the COVID-19 embargo has affected the vast majority of countries in the world, including China [20,21], the United States [22], Europe [23], Russia [24], and elsewhere [25]. Based on ground and satellite measurements, the concentrations of particulate matter (PM 2.5 ), sulfur dioxide (SO 2 ), and nitrogen dioxide (NO 2 ) have dropped significantly in many cities [26][27][28].…”
Section: Introductionmentioning
confidence: 99%